Quantificação de cocaína, benzoilecgonina e anidroecgonina em efluente hospitalar e remoção por fotocatálise e eletrocoagulação - Santos, Jeremias Bastos dos (2016)
In this work we studied an analytical method for identification and quantification of cocaine (COC), benzoylecgonine (BEG) and anidroecgonina (AEG) in effluent samples from the University Hospital of the Federal University of Santa Maria (HUSM). Solid phase extraction (SPE) and dispersive liquid-liquid microextraction (DLLME) were used for extraction and determination of cocaine and its metabolites in the analyzed samples. For SPE we used Chromabond C18® ec 6 ml/500 mg cartridge, yielding recoveries ranging from 73.5% ± 6.3% to 85.0% ± 8.7% in aqueous solution; for the effluent samples, recoveries exceeding 78.0% were obtained when spiked for COC at 15.8 μg L-1 and 195.0 μg L-1; for BEG, at 18.8 μg L-1 and 198.0 μg L-1, and, for AEG, at 30.9 μg L-1 and 210.0 μg L-1. For DLLME we tested different combinations and volumes of solvent extractor/disperser, pH, interaction and extraction times. The best combination of the extraction solvents was of methanol and chloroform at pH 9, adding 0.3 mol L-1 NaCl, 150/350 μL-1 solvent extractor/disperser, resulting in recoveries for COC, in aqueous solution and hospital effluent, ranging from 73.5% to 102.0% (RSD 6.0% and 16.5%). The concentrations found in the HUSM effluent were 2.01 μg L-1 (RSD17.8%) for COC and 1.89 μg L-1 (RSD18.5%) for BEG, which suggests the use of narcotics by patients and/or hospital goers. In order to remove the analytes we applied heterogeneous photocatalysis, using stirred tank reactor fitted with a thermostatic jacket and TiO2 catalyst supported by polydimethylsiloxane (PDMS) bars.Ultraviolet irradiation was carried out with medium pressure mercury vapor lamp (125 W and 401 W m-2). COC and BEG degradation of 97.0% and 93.0% occurred at pH 7 and 40 °C, respectively, after 60 min of irradiation; for the degradation of AEG, the best degradation rate (32,5%) was obtained at pH 5 and 25 °C in aqueous solution; for hospital effluent, the best conditions for the degradation of COC, BEG and AEG were at pH 7 and 30 ° C with degradation rates of 61.0%, 60.0% and 75.0%, respectively. For electrochemical removal of the analytes we used a glass reactor equipped with two pairs of aluminum electrodes with adjustable distance between electrodes, voltage supply reducer, digital multimeter, rheostat and constant stirring. We observed removals of 86.0% and 91.0% for COC and BEG, respectively, for the aqueous solution at pH 3 with the addition of 0.2 mol L-1 NaCl and distance of 6 cm between electrodes. For the hospital effluent best conditions were at pH 7.0, addition of 0.2 mol L-1 NaCl and distance of 10 cm between electrodes, resulting in removals of 72.0% and 88.0% for COC and BEG, respectively. The average concentration of COC and BEG found in the effluent presented low potential environmental impact.